2008
DOI: 10.1063/1.2841124
|View full text |Cite
|
Sign up to set email alerts
|

Allovalency revisited: An analysis of multisite phosphorylation and substrate rebinding

Abstract: The utilization of multiple phosphorylation sites in regulating a biological response is ubiquitous in cell signaling. If each site contributes an additional, equivalent binding site, then one consequence of an increase in the number of phosphorylations may be to increase the probability that, upon dissociation, a ligand immediately rebinds to its receptor. How such effects may influence cell signaling systems is not well understood. Here, a self-consistent integral equation formalism for ligand rebinding, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…Low internal friction and fast chain reconfigurations are therefore expected for short-to-intermediate separations. In a kinetic model of ultrasensitive binding, fast reconfiguration dynamics provides more opportunities for unbound CPDs to (re)bind before pSic1 diffuses out of proximity of Cdc4 [20,21,23]. In the polyelectrostatic model, fast reconfiguration dynamics facilitates pSic1's dynamic interactions with Cdc4 through electrostatic averaging effects [22,25].…”
Section: Conformation-to-function Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low internal friction and fast chain reconfigurations are therefore expected for short-to-intermediate separations. In a kinetic model of ultrasensitive binding, fast reconfiguration dynamics provides more opportunities for unbound CPDs to (re)bind before pSic1 diffuses out of proximity of Cdc4 [20,21,23]. In the polyelectrostatic model, fast reconfiguration dynamics facilitates pSic1's dynamic interactions with Cdc4 through electrostatic averaging effects [22,25].…”
Section: Conformation-to-function Relationshipsmentioning
confidence: 99%
“…Different biophysical models have been proposed to explain the ultrasensitive dependence of the Sic1-Cdc4 interaction on the number of phosphorylated CPDs. A kinetic model argued that the probability of Sic1 rebinding before diffusive exit could exhibit an ultrasensitive dependence on the number of phosphorylated CPDs, dependent on the timescales of diffusion and chain dynamics [20,21]. A polyelectrostatic model suggested that long-range electrostatic interactions between the positively charged CPD binding pocket on Cdc4 and the constellation of unbound negatively charged phosphorylated CPDs on Sic1 could yield ultrasensitive binding [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…1c. The concept was developed by Klein, Pawson and Tyers in 2003 [22] and discussed and elaborated by others [23, 29]. The identical binding sites on the ligand compete for a single binding site on the receptor and only one binding site on the ligand can bind at any given time [22], which is nicely exemplified by multiple phosphorylations on an IDP binding to and competing for the same site [30].…”
Section: Allovalencymentioning
confidence: 99%
“…Please note, that the allovalency model has been discussed and expanded beyond the present formulation by Locasale [29]. …”
Section: Allovalencymentioning
confidence: 99%
“…This feature is found in both natural and synthetic ADs and seems a general feature corresponding to function. We suggest that these clusters function to increase the effective affinity of the AD peptides for their coactivator targets using a mechanism similar to avidity or allovalency -whereby a receptor dynamically interacts with multiple binding sites on a single ligand, effectively inhibiting the dissociation of the two molecules (Locasale, 2008;Olsen et al, 2017). This mechanism fits nicely with the dynamic and fuzzy binding of acidic activators to Med15, and presumably other coactivator targets, as well as the finding that ADcoactivator binding is driven in part by a favorable entropy change Tuttle et al, 2018).…”
Section: Discussionmentioning
confidence: 99%